Music performance anxiety: perceived causes, coping strategies and clinical profiles of Brazilian musicians - Burin,Ana Beatriz (2019)
Abstract Introduction Music performance anxiety (MPA) is characterized by long-lasting, high intensity apprehension associated with performing music in public. At extreme levels, MPA can impair the career and quality of life. Our goal is to describe the clinical profile, perceived causes and coping strategies associated with MPA. Methods In this cross-sectional study, several self-assessment instruments were administered to a sample of 214 Brazilian musicians (68% male, 53.3% classical/46.7% popular musicians). Data were analyzed using descriptive and parametric statistics, based on the variables of musical training and level of MPA. Results Percentages of indicators of pathology were high (40% high MPA levels, 37% social anxiety, 12.5% depression, 13.5% alcohol abuse), and musicians with high MPA levels were the most affected. A wide variety of situations were associated with MPA, especially those related to the individual (pressure from self/concern about audience). Emotion-focused coping and internal resources were prominent among the resources used for coping with MPA (breathing, increased practice, familiarization with performance venue), although they were not always effective. It was relatively uncommon for musicians to seek specialized resources and treatments. Conclusions The results demonstrate the vulnerability of the targeted professional groups and the need for preventive strategies and behavioral, environmental, educational, and pharmacological interventions to change this scenario.